Enhancing the Teaching of Medical Vocabulary Through Content-Based Instruction - Shodieva Gulnoza Nematilloevna (Scientific Trends, 2025)
The article also discusses several teaching strategies that support the implementation of CBI, such as task-based activities, collaborative learning, and project-based learning. These strategies enable students to engage deeply with the content, apply their knowledge in meaningful ways, and build a comprehensive understanding of medical terminology.
Keywords: The article also discusses several teaching strategies that support the implementation of CBI, such as task-based activities, collaborative learning, and project-based learning. These strategies enable students to engage deeply with the content, apply their knowledge in meaningful ways, and build a comprehensive understanding of medical terminology.